2013
DOI: 10.1177/1541931213571348
|View full text |Cite
|
Sign up to set email alerts
|

How Well Do People Rate Their Performance With Different Cursor Settings?

Abstract: Users have many different reasons to choose one product over another and may not be fully aware of why. Understanding these reasons could help Human Factors professionals enhance the user experience by influencing design. In this study, we compared users' subjective ratings of their performances to their actual performances to examine their ability to evaluate their performance during a point and click task using a clickpad. We used seven notebook computers and adjusted the cursor speeds in the control panel. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…A second analysis aimed at improving testing efficiency examined the potential to assess touchpads using 24 trials in a Fitts task, a number similar to the smallest number of trials in the literature (David, Peres & Harper, 2013). Analyses revealed that with 24 participants, 24 trials may be recommended as both 24 and 48 trials were able to demonstrate the significant differences between MT and ER for all target sizes as well as small targets only between the two touchpads.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A second analysis aimed at improving testing efficiency examined the potential to assess touchpads using 24 trials in a Fitts task, a number similar to the smallest number of trials in the literature (David, Peres & Harper, 2013). Analyses revealed that with 24 participants, 24 trials may be recommended as both 24 and 48 trials were able to demonstrate the significant differences between MT and ER for all target sizes as well as small targets only between the two touchpads.…”
Section: Discussionmentioning
confidence: 99%
“…However, while the use of Fitts tasks to assess performance between two touchpads is a common practice, there does not seem to be a widely used standard regarding the number of trials and participants. Specifically, a preliminary review of the literature has revealed that research assessing performance of pointing devices through Fitts tasks range from 10 to 36 participants (Avera, Harper, Russi-Vigoya & Stoll, 2016;Rawdin, Vanderheiden & Lin, 1990;Sawin & Ark, 1999;Sutter & Ziefle, 2005) and from 20 to 640 trials (Bohan, Slocum, Shaikh & Chaparro, 2003;David, Peres & Harper, 2013;Kar, Vu, Nehme & Hedge, 2015). Often, industry practitioners in particular are interested in individual device assessments as well as finding differences between two touchpads.…”
Section: Introductionmentioning
confidence: 99%